The Effect Of Digital Economy On The Growth Of Social Media Users And Non-Cash Economic Transactions: The Effect Of Digital Economy On The Growth Of Social Media Users And Non-Cash Economic Transactions - Sugito Sugito; Megasari Gusandra Saragih (Jurnal Mantik, 2020)
The research objective is to examine the impact of digital economic development on the growth of social media users in conducting non-cash economic transactions. The use of research data with data series ranges from 2012 to 2018. The study uses analysis tools, namely SEM PLS 3.0. The findings obtained in this study are that the digital economy has a positive and significant effect on the growth of social media users. The digital economy has a positive and not significant effect on non-cash economic transactions. The growth of social media users has a negative and not significant effect on non-cash economic transactions. Social media users do not mediate the effect of the digital economy on non-cash economic transactions.